2004
DOI: 10.1002/ijc.20623
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the coxsackie and adenovirus receptor (CAR) on glioma cell growth and invasion: Requirement for the C‐terminal domain

Abstract: Expression of the coxsackie and adenovirus receptor (CAR) is downregulated in malignant glioma cell lines and is barely detectable in high-grade primary astrocytoma (glioblastoma multiforme). We determined the effect of forced CAR expression on the invasion and growth of the human glioma cell line U87-MG, which does not express any CAR. Although retrovirally mediated expression of full-length CAR in U87-MG cells did not affect monolayer growth in vitro, it did reduce glioma cell invasion in a 3-dimensional sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 42 publications
3
44
1
Order By: Relevance
“…These in vitro findings in conjunction with our observations made in cancer tissue specimens suggest that CAR influences gastric cancer cell migration and invasion, hereby contributing to tumour infiltration and dissemination. Again, our data are in line with the limited number of observations made in other tumour entities: Following retrovirally mediated expression of full-length CAR cDNA in a glioma cell line, cultured in a three-dimensional spheroid model, Huang et al observed a reduced cancer cell invasion (Huang et al, 2005). An inhibitory effect of CAR on cancer cell migration has been seen upon CAR upregulation in ovarian and cervical cancer cell lines (Bruning and Runnebaum, 2004).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These in vitro findings in conjunction with our observations made in cancer tissue specimens suggest that CAR influences gastric cancer cell migration and invasion, hereby contributing to tumour infiltration and dissemination. Again, our data are in line with the limited number of observations made in other tumour entities: Following retrovirally mediated expression of full-length CAR cDNA in a glioma cell line, cultured in a three-dimensional spheroid model, Huang et al observed a reduced cancer cell invasion (Huang et al, 2005). An inhibitory effect of CAR on cancer cell migration has been seen upon CAR upregulation in ovarian and cervical cancer cell lines (Bruning and Runnebaum, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…Later on it was identified as a component of the TJ complex, an interacting partner for a number of other TJ proteins, and a regulator of TJ formation (Cohen et al, 2001;Sollerbrant et al, 2003;Coyne et al, 2004;Excoffon et al, 2004;Mirza et al, 2005;Raschperger et al, 2006). On the basis of in vitro assays, it has been speculated that loss of CAR weakens intercellular adhesion, increases proliferation, and promotes migration as well as invasion of cancer cells (Okegawa et al, 2000Runnebaum, 2003, 2004;Huang et al, 2005;Wang et al, 2005). These findings led to the hypothesis of a tumour suppressive role for CAR in human cancers.…”
mentioning
confidence: 99%
“…It may thus be speculated that CAR negatively impacts on these functions, a phenomenon that has already been seen in other tumor cell lines derived from gliomas, ovarian, and cervical cancers. 9,10 However, no significant effect on these functions was seen in the OE19 cell line, limiting the extrapolation of our findings to the situation in vivo. The differences between the tested esophageal adenocarcinoma cell lines may indicate that the suppressive role of CAR on cancer cell migration and invasion depends critically on interactions with other proteins that potentially differ between cell lines.…”
Section: Discussioncontrasting
confidence: 56%
“…This suggests an inhibitory function of CAR on tumor cell growth and is in line with previous observations in human glioma as well as bladder and prostate cancer cell lines. [10][11][12] Furthermore, we noted an increased migration and invasion of OE33 cells following CAR knock down. It may thus be speculated that CAR negatively impacts on these functions, a phenomenon that has already been seen in other tumor cell lines derived from gliomas, ovarian, and cervical cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation